An analysis of saving determinants in Malaysia / Hoo Heap Kgeen - Hoo, Heap Kgeen (2012)
The economic growth rates in Malaysia were relatively higher among Asian countries,especially in the 1990s. Malaysia is also a high savings country in the world, with the savings rates above 25 percent consistently from 1970s to 2000s. This study attempts to examine the relationship and causality between savings and its determinants using annual data from years 1970 to 2010 for Malaysia. The results of JohansenCointegration test show that savings and its determinants, namely real income,dependency ratio, interest rates and foreign savings are cointegrated. There are two long-run cointegrating relationships exist among the variables. Vector Error Correction Model (VECM) approach is employed to estimate the savings equation. In the long run, savings in Malaysia is negatively related to dependency ratio and foreign savings while positively related to real income. On the other hand, short-run savings is negatively related to dependency ratio and interest rates. Therefore, the phenomenon of declining dependency ratio and high economic growth in Malaysia are said to be the main determinants of high savings in Malaysia in the long run. The Granger causality test results reveal that there is a bilateral causality between savings and economic growth, and also between savings and dependency ratio.Nevertheless, interest rates and foreign savings are found to Granger cause savings, and not vice versa. Thus, this study supports both savings-led growth and growth-led savings hypotheses. Based on the stronger causality found from economic growth to savings, Malaysian government should implement more policies to accelerate economic growth rather than policies to stimulate savings in the country.